Photonic flash-annealing of lead halide perovskite solar cells in 1 ms - Joel Troughton (J. Mater. Chem. A, 2016)
An extremely fast annealing technique for mixed-halide perovskite solar cells is presented. Using photonic flash sintering, we have demonstrated that a spin-coated perovskite precursor may be fully annealed in as little as 1 ms. Devices annealed in 1.15 ms yielded power conversion efficiencies (PCEs) of upto 11.3% compared to 15.2% for samples annealed for 90 minutes on a hotplate.